Impact of the second wave of COVID-19 on cancer care at Birat Medical College and Teaching Hospital, Nepal - Sapkota, Sulav; Priyadarshini, Mona (Asian Journal of Medical Sciences, 2022)
Background: The second wave of COVID-19 has plunged Nepal into a public health disaster and has also impacted cancer service to our department of Oncology. Aims and Objectives: To evaluate the impacts of COVID-19 second wave on outpatient department, inpatient department of oncology, Cancer screening, Cancer patients and Healthcare staffs of oncology department respectively. Materials and Methods: We did a prospective descriptive study from April 15, 2021 to June 14 2021 in our Oncology Department at Birat Medical College and Teaching Hospital. All the histopathologically proven cancer patients attending the oncology unit during the specific study periods were taken as study population. Proforma comprising patient details were maintained in excel sheet and the collected data were analyzed with the help of Statistical Package for Social Sciences. Results: We have 78% decrement in outpatient visits and 30% decrement in admissions during the study period. We had 89% reduction in the newly diagnosed cases and total fourteen COVID positive cases. About 50% of the COVID-positive cases expired due to desaturation caused by COVID lung while 50% survived with the medical support. Majority of the infection was due to community spread. PCR test was advised for all the COVID suspects with features of fever and separate isolation ward was implemented for such patients. All of the healthcare staffs of oncology unit were immunized with vaccines as per the government protocol and none of them contracted COVID during the pandemic. Conclusion: Second wave of COVID-19 had a severe impact on cancer service at our Institution. With the decrement in COVID cases and ease of lockdown, slowly we are trying to gain our momentum with utmost COVID precautions.